1986
DOI: 10.1071/bi9860427
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin Response in Border-Leicester X Merino Ewes to Administration of Melatonin, Melatonin Analogues, a Melatonin Metabolite and 6-Methoxybenzoxazolinone

Abstract: The effect of structural modifications of the melatonin molecule on plasma half-life of the analogues and basal prolactin secretion was studied in Border-Leicester x Merino ewes. Halogenation at position 6 and/or unsaturation of the 2,3-double bond of the melatonin molecule slightly lengthened the halflife of the analogues. Melatonin, 6-chloromelatonin, 2,3-dihydromelatonin and 6-chloro-2,3-dihydromelatonin decreased plasma prolactin to 31, 45, 54 and 48% of control levels respectively when administered daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Effects on the reproductive system were also described for both AFMK and AMK, but they remained weaker than those of melatonin [161]. However, contrary to melatonin, no substantial effects of AFMK on prolactin release were observed in ewes [162].…”
Section: Biological and Pharmacological Actionsmentioning
confidence: 99%
“…Effects on the reproductive system were also described for both AFMK and AMK, but they remained weaker than those of melatonin [161]. However, contrary to melatonin, no substantial effects of AFMK on prolactin release were observed in ewes [162].…”
Section: Biological and Pharmacological Actionsmentioning
confidence: 99%
“…In our assay system all three analogues were very potent blockers of puberty. We have previously shown these compounds shared with melatonin potent prolactin-lowering activity in sheep (Kennaway et al 1986). Other groups have also shown that 6-chloro-and 6-fluoro-melatonin derivatives possess full biological potency in various assay systems (Flaugh et al 1979;Martin et al 1980;Vaughn et al 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Other compounds examined were intended to test the hypothesis that melatonin is a prohormone and that the brain metabolites of melatonin, N-acetyl-N 2 -formyl-5-methoxy kynurenamine (aFoMK) and N-acetyl-5-methoxy kynurenamine (aMK) (Hirata et al 1974), may mediate many of the effects ascribed to melatonin itself. In a previous communication we described the use of the prolactin-inhibiting activity of melatonin in sheep as our bioassay (Kennaway et al 1986). In the work discussed in this report we D. 1.…”
Section: Introductionmentioning
confidence: 99%